More than Luck: Australian Protest in a Social Movement Society. Issue 1 (1st July 2019) - Hightower, Ben; East, Scott
Abstract : This introduction begins by challenging a common narrative formed in relation to Australia—that it is a "lucky country." This "exceptionalist" view of Australia is also evidenced in national legal frameworks relating to human rights. Drawing on histories of Australian politics, it is argued that social justice stems not from luck or an exceptional legislative system, but from various forms of social contestation. Especially since the global protests of 2011, more scholars are considering the organization, impacts, and practices of social movements that occur on a global scale. Despite the evolution of globalized protest, this collection is informed by Connell's southern theory (2007), which identifies the unequal geopolitics of knowledge. The articles in this issue provide a diverse range of case studies that can inform protest practices and evidence the vitality of dissent in Australia. Activist knowledges and a quest for collaborative approaches to protest are the two elements that run throughout this issue of Contention.